DEVELOPMENT OF PIEZOELECTRIC HARVESTING SYSTEM AS AN ALTERNATIVE RENEWABLE ENERGY FOR AUTOMATED STREET LIGHT IN MALAYSIA - Kamardan, M.I.F.; Annuar, A.Z.; Zakaria, H.A.; Ahmed, W.; Wan Hassan, W.H. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
In the past few decades, energy consumption for commercial purposes in Malaysia has increased by 100-fold due to escalating development in most states in Malaysia. The intrinsic ability of piezoelectricity to detect mechanical energy and convert it to electrical energy seems to be a promising solution to provide energy for low-power applications of electronic devices, including street lights. It is observed that the street light operation is not effectively managed and consequently caused energy waste. Therefore, this paper aims to exploit the potential of piezoelectric material as an alternative energy supply for automatic street light application. This work consists of three phases, including developing an energy harvesting system, a street light system, and a combination of both systems. A modified piezoelectric design was proposed by sandwiching elastic materials between piezoelectric sensors to increase the mechanical capacity. The result shows that the modified design produced 3.50 V, 30% higher than the commercial piezoelectric design, and capable of supplying low current to the automated street light system. Findings from this study might reduce energy consumption by a street light and indirectly provide a more sustainable way to supply electricity to street lamps.